Insight into the Stereocontrol of DNA Polymerase‐Catalysed Reaction by Chiral Cobalt Complexes. Issue 16 (27th June 2022) - Wu, Ya; Bu, Xinya; Ke, Yongqi; Sun, Huaming; Li, Jingyao; Chen, Lu; Cui, Wei; He, Yujian; Wu, Li
Abstract: Enantiomers of chiral substances typically have distinct biological activities, thus, the explorations of biochemical processes at the enantiomeric level has very high significance. This study investigated DNA polymerase–catalyzed reaction modulated by various types of chiral cobalt complexes. The experimental data showed that polymerase reactions were inhibited or accelerated in the presence of K[Co(edta)] ⋅ 2H2 O or [Co(en)3 ]I3 ⋅ H2 O. More importantly, the stereocontrol of bioreactivity was found to be different for the enantiomers, which was reflected in their ability to bind to the polymerase reaction system. The docking simulation illustrated that the acceleration or inhibition of polymerase reaction could be correlated with diverse electrostatic energy induced by the attached metal chelates, whereas the different stereocontrol of bioreactivity for the enantiomers was attributed to a discrepancy of Van der Waals interactions between the enantiomer and polymerase catalytic sites. Abstract :